The Effect of Relationship Quality on Continuity in the Use of Sharia M-Banking: The Role of Access Convenience, Service Quality and Structure Assurance - Wibowo, Ardy; Wibowo, Febrian Wahyu; Sujono, Rusny Istiqomah; Wibisono, Dimas; Khasanah, Uswatun (EKONOMIKA SYARIAH : Journal of Economic Studies, 2023)
Abstrak This research delves into the impact of relationship quality (RQ) on the ongoing utilization of sharia mobile banking (m-banking). The study draws upon the Theory of Planned Behaviour (TPB) and past behaviour as theoretical frameworks to examine how sustainability attitudes influence the use of m-banking, considering the quality of customer relationships with banks in determining sustainable intentions in sharia m-banking usage. Employing a quantitative approach, the research involves data collection, interpretation, and presentation based on a sample of 100 sharia m-banking users in the Special Region of Yogyakarta, using Snowball Sampling. Questionnaires were distributed for data collection, and the analysis utilized the Structural Equation Modelling (SEM) method with the Partial Least Square (PLS) program. The findings support all four hypotheses, indicating significant effects on sustainability intentions in sharia m-banking usage. The study also conducted mediation testing, revealing that variables such as Access Convenience and Service Quality do not directly impact sustainability intentions. Instead, a good-quality relationship with the provider is essential for sustainable intentions in sharia m-banking, while the Structural Assurance variable directly influences sustainable intentions without necessitating a high-quality relationship with the bank.Â Penelitian ini menyelidiki dampak kualitas hubungan (RQ) terhadap pemanfaatan mobile banking (m-banking) syariah yang sedang berlangsung. Studi ini mengacu pada Theory of Planned Behavior (TPB) dan perilaku masa lalu sebagai kerangka teoritis untuk menguji bagaimana sikap keberlanjutan mempengaruhi penggunaan m-banking syariah, dengan mempertimbangkan kualitas hubungan nasabah dengan bank dalam menentukan niat berkelanjutan dalam penggunaan m-banking syariah. Dengan menggunakan pendekatan kuantitatif, penelitian ini melibatkan pengumpulan, interpretasi, dan penyajian data berdasarkan sampel 100 pengguna m-banking syariah di Daerah Istimewa Yogyakarta, dengan menggunakan Snowball Sampling. Kuesioner disebar untuk pengumpulan data, dan analisisnya menggunakan metode Structural Equation Modeling (SEM) dengan program Partial Least Square (PLS). Temuan ini mendukung keempat hipotesis, yang menunjukkan dampak signifikan terhadap niat keberlanjutan dalam penggunaan m-banking syariah. Studi ini juga melakukan pengujian mediasi, yang menunjukkan bahwa variabel seperti Kenyamanan Akses dan Kualitas Layanan tidak berdampak langsung terhadap niat keberlanjutan. Sebaliknya, hubungan berkualitas baik dengan penyedia layanan sangat penting untuk niat berkelanjutan dalam m-banking syariah, sedangkan variabel Jaminan Struktural secara langsung mempengaruhi niat berkelanjutan tanpa memerlukan hubungan berkualitas tinggi dengan bank.